The effect of the strategy of questions in developing the thinking skills - Hamid, Raida Hussein; Mousa Al-Zwaini, Ibtisam Sahib (Opción, 2019)
The study aims to investigate the effect of the strategy of cluster questions in developing the thinking skills of the scientific fourth grade of female students in literature and text material via statistical boot (SPSS). As a result, teaching according to the strategy of the cluster influenced the development of intelligent thinking among the students of the experimental group. In conclusion, the strategy of the cluster helped to increase the students' effectiveness and their love for the material. The strategy of the cluster helped to develop the intelligent thinking of students through a lot of thinking, discussion, research and interpretation.